Mapping of Self-Efication and Performance of Equality Tutors Implementing Learning Duties in SKB Kota Pekanbaru - Wilson, Wilson; Ayub, Daeng (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to determine how self efficacy and performance of Equality Package tutors in Pekanbaru City SKB, is there a relationship between self-efficacy and performance in the implementation of learning tasks. The study was conducted in Pekanbaru city with respondents all tutors who were members of SKB Pekanbaru City who were honored 20 people. As a survey research, data using questionnaire (questionnaire). Data processed with percentages and results are: (1) self-efficacy with three dimensions, an average of 89.99% believe in their ability to adjust the tasks assigned to them. (2). The performance of tutors in carrying out learning tasks with four sub, averaging 82.35% who have carried out their duties (3) The link between self-efficacy and tutor performance, the results of which are data analysis with chi square using SPSS, that is, chi count of 0.333, df 1 and a significant accumulation of 0.564 with 0.05%. Chi Square table value at df 1 (0.05%) is 3.841. Thus the chi square value is smaller than the chi square table value, then the proposed hypothesis is rejected. There is a relationship between self-efficacy and tutor performance in carrying out learning tasks.